Intrusion et exclusion dans les romans politiques de Trollope - Laurent Bury (Cahiers Victoriens et Edouardiens)
The Victorian « sense of belonging » is studied in Anthony Trollope’s last two Political novels. The Prime Minister (1876) offers a perfect illustration of the traditional pattern Intrusion-Exclusion : a social climber tries to creep into the upper classes but his star soon pales, which eventually leads him to suicide. In The Duke’s Children (1880), one finds a more surprising case of opening to the Other, when Plantagenet Palliser’s son, Lord Silverbridge, marries a young American commoner. While Trollope multiplies the metaphors expressive of social exclusion, the narration itself seems to open itself to the reader so as to include the reader within the writer’s laboratory.